Impact of DAESI Program on Trained Input Dealers: a Perception Study - Balasubramani, N (Journal of Agricultural Extension Management, 2018)
Most of the farmers in India seek farm advice from Input dealers. However, majority of these input dealers do not have technical knowledge on Agriculture. Hence, the National Institute of Agricultural Extension Management (MANAGE) launched an innovative program namely, â€œDiploma in Agricultural Extension Services for Input Dealers (DAESI)â€ to enhance the technical competency of input dealers. This program is conducted in 11 states. A Perception Study was conducted to analyze the impact of DAESI Program on trained input dealers, by taking 10 per cent of the sample randomly from all the 11 states. The significant findings of the study reveal that there is a positive trend of young people with higher qualifications joining DAESI Program; majority of them are small retailers or selling more than one category of agri inputs; most of the trained input dealers felt that topics covered in the class room, study material given to them and field visits organized were most relevant to them. The level of satisfaction with class room sessions and exposure visits was very good. Majority perceive that they have fully gained Knowledge and Skills on various aspects of agriculture, and gained confidence in technology dissemination, which are sufficient to give suitable advice to field level problems of farmers. Majority felt that their customer base and sale of inputs have increased and they have changed their approach in analyzing the field problems after DAESI Program.